Answers

  • Brainly User
2016-03-01T18:28:36+08:00
1/b + 1/(b + 12) = 1/8

Multiply each term by LCD   (b) (b + 12) (8)

(b)(b+12)(8)(1/b) + (b)(b+12)(8)(1/b+12) = (b)(b+12)(8)(1/8)

8b + 96 + 8b = b² + 12b

Arrange as quadratic equation in the form ax² + by + c = 0

b² + 12b - 8b - 8b - 96 = 0

b² - 4b -  96 = 0

Solve by factoring:
b²  - 4b - 96 = 0

(b - 12) (b + 8) = 0

b - 12 = 0           b + 8 = 0
b₁ = 12               b ₂ = - 8





0
Soooooooooooooooooooooo long
If i give you a short cut solution, you won't be able to understand how it becomes a quadratice equation.
** quadratic equation. If you follow those steps, you can solve similirar problems